The main changes in the Lithuanian economy development in the transition to market economy - Ciburienë J. (Selected readings on economies in transition, 2000)
The development of the economy until 1990 in Lithuania, as a composite part of the Soviet Union (the USSR), was based on totalitarian governing elements. Until 1989, the perspective of development of socialist property was tied together with the growing role of state property. It was estimated that the more economic process was rendered into the state property, the more developed society was. This caused a great deal of damage to the economic development. The purpose of this paper is to investigate the main changes of the development process in the Lithuanian economy. The difficulties of the economic development were displayed in the country's economy as a disproportion between demand and supply (producers dictate for consumers). Directive pricing, a monopolised economy, a centralised distribution system of production and administrative-command methods of governing were used.